A Generic Conversion Strategy: From 2D Metal Carbides (MxCy) to M‐Self‐Doped Graphene toward High‐Efficiency Energy Applications. (11th January 2017) - Kou, Zongkui; Meng, Tian; Guo, Beibei; Amiinu, Ibrahim Saana; Li, Wenqiang; Zhang, Jie; Mu, Shichun
Abstract : This study first presents a subtle thermal‐chlorination strategy for a universal transformation of abundant 2D metal carbides (M x C y, e.g., Cr3 C2, Mo2 C, NbC, and VC) to 2D graphene and M‐self‐doped graphene (MG). The as‐obtained MG endows a transparent sheet architecture of one to four atomic layers. Simultaneously, MG with different M amounts is synthesized by tuning the chlorination parameters. Among them, the novel and representative Cr‐self‐doped graphene with optimal Cr amount (4.81 at%) demonstrates the outstanding electrochemical performance. It presents an energy density of 686 W h per kg electrode and a power density of more than 391 W per kg electrode as anode material of Li ion batteries, and four‐fold activity against the commercial iridium oxide electrode toward oxygen evolution reaction as well as a comparable oxygen reduction reaction performance to the commercial platinum catalyst. Moreover, this method is readily scalable to produce graphene and MG electrode materials on industrial levels. Abstract : For the first time, graphene and its derivative metal‐self‐doped graphene (MG) are obtained by a universal technique to thermal chlorination of 2D metal carbides (M x C y ). Comparing with top nonmetallic atoms‐doped graphene, particular MG demonstrates superb Li‐storage properties as anode of LIBs and catalyticalctivities for oxygen reduction and evolution reactions.